Cutaneous Leiomyosarcoma of the Face - Kim, Nam Gyun; Kim, Jun Oh; Park, Young Ji; Kim, Jun Sik; Lee, Yoon Jung; Lee, Kyung Suk (Archives of craniofacial surgery, 2017)
Cutaneous leiomyosarcoma is an uncommon superficial soft tissue sarcoma and mainly found in the middle aged to elderly males. It can occur in any part of the body, mostly affecting the extremities and rarely affecting the face. It grows relatively slowly, can be diagnosed by biopsy and is treated by surgical excision. It needs to be distinguished from other spindle cell neoplasms, and immunohistochemical markers are usually required to attain an accurate diagnosis. We report a case of cutaneous leiomyosarcoma appeared on the left cheek within 6 month of a 73-year-old female patient suspected with malignant melanoma before surgery.